A Novel Missense Variant in Actin Binding Domain of MYH7 Is Associated With Left Ventricular Noncompaction - Hesaraki, Mahdi; Bora, Ugur; Pahlavan, Sara; Salehi, Najmeh; Mousavi, Seyed Ahmad; Barekat, Maryam; Rasouli, Seyed Javad; Baharvand, Hossein; Ozhan, Gunes; Totonchi, Mehdi (Frontiers in Cardiovascular Medicine, 2022)
Cardiomyopathies are a group of common heart disorders that affect numerous people worldwide. Left ventricular non-compaction (LVNC) is a structural disorder of the ventricular wall, categorized as a type of cardiomyopathy that mostly caused by genetic disorders. Genetic variations are underlying causes of developmental deformation of the heart wall and the resultant contractile insufficiency. Here, we investigated a family with several affected members exhibiting LVNC phenotype. By whole-exome sequencing (WES) of three affected members, we identified a novel heterozygous missense variant (c.1963C>A:p.Leu655Met) in the gene encoding myosin heavy chain 7 (MYH7). This gene is evolutionary conserved among different organisms. We identified MYH7 as a highly enriched myosin, compared to other types of myosin heavy chains, in skeletal and cardiac muscles. Furthermore, Myh7 was among a few classes of Myh in mouse heart that highly expresses from early embryonic to adult stages. In silico predictions showed an altered actin-myosin binding, resulting in weaker binding energy that can cause LVNC. Moreover, CRISPR/Cas9 mediated myh7 knockout in zebrafish caused impaired cardiovascular development. Altogether, these findings provide the first evidence for involvement of p.Leu655Met missense variant in the incidence of LVNC, most probably through actin-myosin binding defects during ventricular wall morphogenesis.